The impact of Covid-19 and government policies on the liquidity of Indonesia Stock Exchange - I Gde Reza Rizky Margana; Buddi Wibowo (President University, 2022)
Generally, the main characteristics of emerging markets are low transparency, and the investors in emerging markets are more likely to be short-term oriented, where short-term investors are usually concerned about the liquidity of securities they will trade. These may imply liquidity has important role in emerging markets than in developed markets. Empirical studies have confirmed sporting events, exceptional events, political events, social media content, natural disasters, and religious events may affect the liquidities of capital market. This study aims to identify the effect of Covid-19 and government policies on the liquidity of the Indonesia Stock Exchange. Measurement of liquidity in this study using Amihud Illiquidity. The sample of this research is all stocks listed on the Indonesia Stock Exchange for the period 02 March – 02 June 2020. The results of this study indicate that the independent variables simultaneously affect the liquidity of the emerging stock market of the Indonesia Stock Exchange, while the independent variables that partially affect the liquidity of the Indonesia Stock Exchange are restrictions on the activities of educational institutions, restrictions on workplace activities, control of international travel, transaction volume, and BI rate.